Programming mechanical metamaterials using origami tessellations. (22nd March 2020) - He, Y.L.; Zhang, P.W.; You, Z.; Li, Z.Q.; Wang, Z.H.; Shu, X.F.
Abstract: Origami structures, whose mechanical properties can be tuned by programing the crease network, have been sought in application including DNA origami nanorobots and deployable space structures. However, the existing researches mainly placed on the cylindrical origami tubes or the periodic cellular metamaterials, which are based on the stacking of individual 3D origami units. Here, we present a novel mechanical metamaterial, which can be constructed via using the curved-crease origami (CCO), with tunable Poisson's ratio and stiffness. We further analytically and experimentally demonstrate that the Poisson's ratio of these structures exhibits some new properties by altering the length to width ratio of the structures. In addition, we verify the tunable stiffness of the CCO-based metamaterials by changing the patterns of these structures. Our approach can be used to design and construct the next generation of the CCO-based metamaterials with tunable mechanical properties for engineering applications.